Exploring networks of care in implementing midwife-led birthing centres in low- and middle-income countries: A scoping review. - Sabera Turkmani; Andrea Nove; Oliva Bazirete; Kirsty Hughes; Sally Pairman; Emily Callander; Vanessa Scarf; Mandy Forrester; Shree Mandke; Caroline S E Homer (PLOS Global Public Health)
The evidence for the benefits of midwifery has grown over the past two decades and midwife-led birthing centres have been established in many countries. Midwife-led care can only make a sustained and large-scale contribution to improved maternal and newborn health outcomes if it is an integral part of the health care system but there are challenges to the establishment and operation of midwife-led birthing centres. A network of care (NOC) is a way of understanding the connections within a catchment area or region to ensure that service provision is effective and efficient. This review aims to evaluate whether a NOC framework-in light of the literature about midwife-led birthing centres-can be used to map the challenges, barriers and enablers with a focus on low-to-middle income countries. We searched nine academic databases and located 40 relevant studies published between January 2012 and February 2022. Information about the enablers and challenges to midwife-led birthing centres was mapped and analysed against a NOC framework. The analysis was based on the four domains of the NOC: 1) agreement and enabling environment, 2) operational standards, 3) quality, efficiency, and responsibility, 4) learning and adaptation, which together are thought to reflect the characteristics of an effective NOC.Of the 40 studies, half (n = 20) were from Brazil and South Africa. The others covered an additional 10 countries. The analysis showed that midwife-led birthing centres can provide high-quality care when the following NOC elements are in place: a positive policy environment, purposeful arrangements which ensure services are responsive to users' needs, an effective referral system to enable collaboration across different levels of health service and a competent workforce committed to a midwifery philosophy of care. Challenges to an effective NOC include lack of supportive policies, leadership, inter-facility and interprofessional collaboration and insufficient financing. The NOC framework can be a useful approach to identify the key areas of collaboration required for effective consultation and referral, to address the specific local needs of women and their families and identify areas for improvement in health services. The NOC framework could be used in the design and implementation of new midwife-led birthing centres.